THE OCCURENCE OF CAUSAL FUNGUS OF BANANA LEAF SPECKLE, ON PSEUDOSTEM OF MUSA X PARADISIACA IN INDONESIA - Desi Maria Panjaitan; Nampiah Sukarno; Mien Ahmad Rifai (Floribunda, 2016)
The banana leaf parasite hyphomycete Ramichloridium musae is recorded for the first time on dried banana pseudostem from Java.